The European Court of Human Rights’ Engagement with International Human Rights Instruments: Looking at the Cases of Domestic Violence - Demir, Ebru (The Age of Human Rights Journal, 2021)
In its recent jurisprudence on domestic violence, the European Court of Human Rights started to examine the domestic violence cases in the light of relevant international human rights law developed in this specific area. This article examines the engagement of the European Court of Human Rights with other international and regional human rights instruments in domestic violence cases. Upon examination, the article concludes that by integrating its case law into international human rights law the European Court of Human Rights broadens the scope of protection for domestic violence victims and maintains the unity of international law.